2015
DOI: 10.1371/journal.pone.0126954
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative and Immunogenic Characteristics of Cultured Nucleus Pulposus Cells from Human Cervical Intervertebral Discs

Abstract: Cell-based regenerative approaches have been suggested as primary or adjuvant procedures for the treatment of degenerated intervertebral disc (IVD) diseases. Our aim was to evaluate the regenerative and immunogenic properties of mildly and severely degenerated cervical nucleus pulposus (NP) cells with regard to cell isolation, proliferation and differentiation, as well as to cell surface markers and co-cultures with autologous or allogeneic peripheral blood mononuclear cells (PBMC) including changes in their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Moreover, inflammatory factors were found to have increased expression in the study of Takada et al, who found IVD autografts induced TNFα, IL-6 and IL-8; as well as cyclooxygenase 2 up-regulation and macrophage infiltration in sciatica [46]. By co-culture of autologous or allogeneic peripheral blood mononuclear cells and NP cells, Stich et al found elevated immune cell proliferation levels in 3Dcultures than 2D-cultures, and a general trend to higher responses for NP cells from severely degenerated IVD tissue [47], indicating that autoimmune response could vary depending on different cell cultures and degeneration degrees. More recently, Silva et al established a model of IVD organ culture, found that human macrophages could be polarized toward a more pro-inflammatory profile by degenerated IVD tissue, and interfere with IVD ECM remodeling by downregulating aggrecan and collagen II gene expression in the presence of IL-1β [48].…”
Section: Auto-immune Response Of the Npmentioning
confidence: 96%
“…Moreover, inflammatory factors were found to have increased expression in the study of Takada et al, who found IVD autografts induced TNFα, IL-6 and IL-8; as well as cyclooxygenase 2 up-regulation and macrophage infiltration in sciatica [46]. By co-culture of autologous or allogeneic peripheral blood mononuclear cells and NP cells, Stich et al found elevated immune cell proliferation levels in 3Dcultures than 2D-cultures, and a general trend to higher responses for NP cells from severely degenerated IVD tissue [47], indicating that autoimmune response could vary depending on different cell cultures and degeneration degrees. More recently, Silva et al established a model of IVD organ culture, found that human macrophages could be polarized toward a more pro-inflammatory profile by degenerated IVD tissue, and interfere with IVD ECM remodeling by downregulating aggrecan and collagen II gene expression in the presence of IL-1β [48].…”
Section: Auto-immune Response Of the Npmentioning
confidence: 96%
“…Stich et al indicated that cell-based regenerative approaches could be advised as a primary or adjuvant procedure in order to prevent degeneration in IVD treatment (24). They tested middle-and upper-level degenerated cervical NP cells in terms of cell renewal, proliferation, and differentiation.…”
Section: █ Discussionmentioning
confidence: 99%
“…However, Okuma et al ( 9 ) reported that the reinsertion of stimulated NPCs delayed IVD degeneration. NPCs were also used to build 3D tissue engineering complexes to repair IVD ( 28 ). Ganey et al ( 18 ) demonstrated that DC transplantation was a viable treatment for degenerated or damaged IVD.…”
Section: Discussionmentioning
confidence: 99%